2008
DOI: 10.1111/j.1440-1746.2008.05404.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel single nucleotide polymorphism of the VEGF gene as a risk predictor for gastroduodenal ulcers

Abstract: The novel VEGF polymorphism -1780T/C could significantly predict the predisposition to GDU after the exposure to etiologic risks, based on defective angiogenic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…It has been demonstrated that the C936T SNP in the 3'-UTR of the VeGF gene is associated with a reduced serum level of cytokine (69,70). More recently, a novel SNP in the VeGF promoter (-1780 T/C), which was found to significantly affect gene expression, has been described (67). The authors reported a strong relationship between this SNP and the occurrence of gastroduodenal ulcers.…”
Section: Tnf Gene Variantsmentioning
confidence: 81%
See 2 more Smart Citations
“…It has been demonstrated that the C936T SNP in the 3'-UTR of the VeGF gene is associated with a reduced serum level of cytokine (69,70). More recently, a novel SNP in the VeGF promoter (-1780 T/C), which was found to significantly affect gene expression, has been described (67). The authors reported a strong relationship between this SNP and the occurrence of gastroduodenal ulcers.…”
Section: Tnf Gene Variantsmentioning
confidence: 81%
“…Moreover, they confirmed that the transfection of the HMeC-1 endothelial cell line with the -1780 T/C SNP-containing vector influenced the angiogenic activity of these cells in vitro. Indeed, cells transfected with this mutant vector displayed repressed promoter activity as compared to cells transfected with the wild-type vector, and subsequently displayed impaired angiogenic potential (67).…”
Section: Tnf Gene Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In RAU, the most common oral mucosal disease, the salivary levels of VEGF have been also associated with oral ulceration [52]. Finally, genetic variation in the VEGF gene has been also associated with the risk of developing gastroduodenal ulcers [53]. Evidence from these studies implicates angiogenesis in the pathophysiological development of oral ulcers, at both the genetic and at the functional level.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al. evaluated whether the vascular endothelial growth factor (VEGF) polymorphism could predict susceptibility to PUD through modified angiogenic activities and found that the VEGF polymorphism ‐ 1780T/C could significantly predict the predisposition to PUD after exposure to etiologic risks [12]. To understand the importance of this polymorphism, previously reported SNPs, such as IL‐1β and TNF‐α, are needed for a comparative study.…”
Section: Gastroduodenal Ulcer and H Pylori Infectionmentioning
confidence: 99%